Errors in the information (data) contained in the Unified State Register of Legal Entities: types and methods of elimination - A. V. Gabov (Правоприменение)
The subject of research. The issue of reliability (unreliability) of information (data) included in the Unified State Register of Legal Entities has increased after the amendments made to the Russian Civil Code in 2013 and to the Russian legislation on state registration of legal entities in 2015. The legislation, introducing the principle of public reliability of information included in the Unified State Register of Legal Entities does not clearly define what is meant by such reliability. Accordingly, the question arises about what is meant by “unreliability” of information. Although legal norms contain the concept of “error”; the legislation does not contain a single legal regime of “error”. This is expressed in the presence of several independent cases described in the legislation, including, among other things, an independent procedure for correcting an error. It is also not clear how the presence of an “error” correlates with the requirements for the reliability of the data of the Unified State Register of Legal Entities. The author shows the evolution of the concepts of “error” and “technical error” in the legislation on state registration of legal entities, as well as ways to eliminate it for the first time in the Russian doctrine.The purpose of the article is to: (a) analyze the current regulation and qualify various cases of “errors” in the information included in the Unified State Register of Legal Entities; (b) specify the objectives of regulation in each identified case of “errors”; (c) identify the main contradictions in the regulation; (d) form a new model of the reliability of the information included in the Unified State Register of Legal Entities and specific legal decisions based on the goals of the legislator to “whitewash” the Russian economy, strengthen the principle of good faith, and ensure the certainty of legal norms. The scientific hypothesis is that the “error” in the information included in the Unified State Register of Legal Entities, whatever its cause, is a special case of unreliability of information. Accordingly, all cases of “error” should be settled within the framework of the general model of reliability of information included in the Unified State Register of Legal Entities. The current regulation does not provide real public reliability of the information; in fact, such public reliability today is nothing more than an illusion. Approaches to determining the reliability (unreliability) of information included in the Unified State Register of Legal Entities do not provide such reliability.Description of research methods and methodology. The research is based on a systematic and teleological interpretation of normative material (legal norms, explanations of a normative nature, judicial legal positions). Information about the main scientific results. Conclusions. The conducted research fully confirmed the correctness of the proposed scientific hypothesis. Systematic proposals for changing existing approaches to regulation and specific legal solutions are formulated. Conclusions. It is noted that the current regulation regarding the criteria for the reliability/unreliability of information (data) of the Unified State Register of Legal Entities is confusing and creates uncertainty in the legal regulation. The necessity of changing the norms of the Civil Code of the Russian Federation and other federal laws, the abolition of the most odious explanations of a regulatory nature, the foundations of a new regulatory model and proposals for reforming the existing regulatory framework are formulated.